The Importance of the Oil and Gas Complex for the Brazilian Economy and Its States - Joaquim Jose Martins Guilhoto; Silvio Massaru Ichihara; Fernando Antonio Slaibe Postali (European Regional Science Association (ERSA), 2006)
This paper presents the results of a research conducted to measure the importance of the oil and gas complex in the Brazilian economy and in its states. Initially, the efforts were concentrated in the construction of an interregional input-output system for the 27 states of the Brazilian economy at the level of 42 industries, for the year of 2002. Using this system it was possible to make an analysis of role played by the oil and gas complex in the Brazilian economy and its states. First it is made an analysis of the economic flows linked with the oil and gas production, and then it is made an estimation of the GDP value generated by the oil and gas complex in the Brazilian economy and its states. It is also made an analysis in detail of the productive chain of the oil and gas, starting from the suppliers of inputs to the oil and gas production, going through the production itself and the various stages of refining and processing, and ending at the measuring of the services and distribution activities. The results show that the oil and gas complex has a share of around 10.4% of the Brazilian GDP, while the share in the GRP of the states can go from less than 1% to 27%.
Keywords: 330